ANALISIS PERIMBANGAN KEUANGAN PUSAT DAN DAERAH : STUDI KASUS TUNTUTAN PROVINSI RIAU TERHADAP DANA BAGI HASIL SUB SEKTOR PERKEBUNAN KELAPA SAWIT - Hasaniarto "; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aimed (1) to find out why the emergence of demands Balance fund and the Regional Financial Center in the form of profit sharing fund (DBH) of oil palm sub-sector. The study also aimed (2) to determine the basis for determining why there needs to be funding the Central and Regional Financial Balance of oil palm sub-sector. In addition, this study also aims. (3) To know how the implementation of the financial balance between the Central Government and the Local Government sub-sector of oil palm plantations located in Riau Province.This study is a qualitative research, the data collection techniques in this research is descriptive analysis. This study uses the documentation and interview with key informants as an object of information that aims to achieve the goal in order to obtain the information in the study. Data used in this study are primary data and secondary data obtained through documentation, and interviews with key informants in this study.The results showed that (1) the motivation of Riau Province to obtain DBH of CPO export duties is, a sense of injustice, in the distribution management of state revenues, especially from sectors this CPO export tax. (2) By adopting the sixth fiscal transfer eligibility criteria commonly used by many countries in the world. namely, otonomi (Autonomy), penerimaan yang memadai (revenue adequacy), keadilan (equity), Transparansi dan stabilitas (transparance and stability), sederhana (simplicity) dan insentif (incentif),, then the state's revenue from export tax for CPO worthy been distributed. (3) since the implementation of the financial balance of the sub-sectors of oil palm plantations, has not reflected the sense of justice of the area.Keywords: balancing funds, revenue-sharing (DBH), fiscal transfers, sub-sector oil palm plantations, CPO export duties.